2020
DOI: 10.1021/acs.estlett.9b00702
|View full text |Cite
|
Sign up to set email alerts
|

Nontargeted Tandem Mass Spectrometry Analysis Reveals Diversity and Variability in Aerosol Functional Groups across Multiple Sites, Seasons, and Times of Day

Abstract: Organic aerosol (OA) is a complex mixture of compounds with diverse elemental and structural features, and its composition affects its health and environmental impacts. A detailed speciation of the functional group distribution in OA is important for constraining atmospheric reaction pathways and products, evaluating chemical mechanisms and models, and understanding OA impacts. We used high-resolution tandem mass spectrometry to perform a nontargeted analysis of OA functional groups from three diverse ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 101 publications
7
86
0
2
Order By: Relevance
“…As such, we limited the following adsorbent tube data analysis to compounds in the C 10 -C 25 range to focus on intermediate-volatility and semivolatile compounds (I/SVOCs) present in the gas phase. In our analyses and interpretation, the compounds included in each of these volatility ranges are defined based on fixed values of saturation mass concentrations (e.g., Donahue et al, 2011;Murphy et al, 2014) at the observed 18-22 µg/m 3 OA loadings present during adsorbent tube sampling times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we limited the following adsorbent tube data analysis to compounds in the C 10 -C 25 range to focus on intermediate-volatility and semivolatile compounds (I/SVOCs) present in the gas phase. In our analyses and interpretation, the compounds included in each of these volatility ranges are defined based on fixed values of saturation mass concentrations (e.g., Donahue et al, 2011;Murphy et al, 2014) at the observed 18-22 µg/m 3 OA loadings present during adsorbent tube sampling times.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed via liquid chromatography (Agilent 1260 LC) with electrospray ionization (ESI) and the same Q-TOF. For filters, the ESI source was operated in both positive and negative ionization modes, and the Q-TOF was operated in both MS mode (i.e., TOF data collection, "LC-ESI-MS") and MS/MS mode (i.e., tandem mass spectral data collection, "LC-ESI-MS/MS") (Ditto et al, , 2020. Filter extracts were also analyzed using GC-APCI-MS in positive ionization mode.…”
Section: Methodsmentioning
confidence: 99%
“…al., 1997;Kalberer et al, 2004;Berndt et al, 2005;Jimenez et al, 2009;Kirkby et al, 2011). Heterogeneous reactions may also further increase the complexity of ambient aerosol mixtures (George and Abbatt 2010;Ditto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that these values may be close to representative for a range of hydroxy nitrates. This rapid aqueous-phase hydrolysis can explain the difficulty to detect the presence of substantial aerosol phase organic nitrates under ambient conditions (Ditto et al, 2020). As hydroxy nitrate production can represent an important fate for daytime oxidation of isoprene and terpenes in forest-impact environments, the uptake of these compounds into acidic aerosol followed by hydrolysis can represent an important mechanism for conversion of NOx to HNO3, as discussed in Romer Present et al, 2019 andZare et al, 2018. While the fate of the resulting diol in solution is unclear, there is a range of possible processes in the aqueous phase, including OH radical attack and oligomerization.…”
Section: Aqueous Phase Hydrolysismentioning
confidence: 99%
“…These low volatility, water-soluble compounds are important precursors to and constituents of SOA due to their efficient partitioning with the condensed-phase (Biesenthal et al, 1997;Fry et al, 2009Fry et al, , 2014Perraud et al, 2012;Rollins et al, 2012). Ambient measurements have indicated that up to 23% of molecules in organic aerosol contain the RONO2 functional group, suggesting RONO2 represent a significant fraction of BVOC-derived oxidation products (Ditto et al, 2020;Rollins et al, 2013). However, the hydrolysis lifetime in the aerosol phase (~1-3 hours) is much shorter than the lifetime of the aerosol itself (~1 week), which suggests the contribution of organic nitrates to aerosol mass may have been underestimated from the observational data (Romer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%